THE QUESTION OF MODERN SYSTEMATIZATION OF DENTAL CARIES IN UKRAINIAN CHILDREN - L. Khomenko; N. Bidenko (Український стоматологічний альманах)
To represent the scientific achievements of Ukrainian dental researches we have to use modern terms and classifications accepted by most countries concerning to main stomatological diseases. It is particularly important in paediatric dentistry due to many peculiarities of children’s dental caries and high possibility of its prevention on early stages of tooth developing.